Public support for vegetarian meals in public canteens: a preliminary study - Cardoso, Sónia (2018)
In 2016 the United Nations implemented the 2030 Agenda for Sustainable Development with 17 Sustainable Development Goals and 169 targets pertaining to the economic, social, and environmental dimensions. Scientific evidence suggests that of the 17 goals, at least six would be closer to being accomplished1 if the Global West transitioned to a more plant-based diet.2 In 2006 a fao (Food and Agriculture Organization of the United Nations) report identified the livestock sector as “by far the single largest anthropogenic user of land” (Steinfeld et al. 2006, xxi) since it uses no less than 70% of all agricultural land and 30% of the land surface of the planet. This amount of production takes its toll on the environment: the livestock sector operates as a big influencer in climate change, reportedly responsible for 18% of greenhouse gas emissions – a share higher than all transports taken together. The sector is also stated to be one of the greatest contributors to water pollution and biodiversity loss (possibly even being the primary cause) due to its role in deforestation and in “land degradation, pollution, climate change, overfishing, sedimentation of coastal areas and facilitation of invasions by alien species” (Steinfeld et al. 2006, xxii and xxiii).